Sustainable and cost-efficient feed ingredients for optimum breeding of house crickets (Acheta domesticus) for human consumption in Thailand - von Hackewitz, Lina (2021)
The world population is expected to increase over the next 30 years. The global food production system is under pressure to keep up with the growing demand . In the last years, increased attention has been paid to use livestock with lower environmental impact, like the house cricket Acheta domesticus. In Thailand’s northern and north-eastern regions, entomophagy has been a tradition since the past. House crickets are farmed due to their capacity to utilise resources, more efficiently than traditional livestock. They can be fed with wide variety of plant material, such as byproducts and food waste from food industry and agriculture. The quality of the house crickets depends to a great degree on the quality, consistency and composition of the feed. To sus-tain optimal growth, cricket farmers are traditionally using high-protein chicken feed (approximately 21% protein). However, the chicken feed con-taining soy- and fish meal is not sustainable. In this study some cost efficient and sustainable feed ingredients for soy- and fish meal for the in Thailand widely-used edible insect species, house cricket (Acheta domesticus), was investigated. The crickets were fed on feeds where soy- and fish meal was replaced with more sustainable products, such as food-industrial byproducts and weeds and which can be adapted to large-scale farm industry in Thailand. Three experimental feeds and one control feed were applied, to study the growth rate, survival rate and feed- and water use and feed conversion rate (FCR). The results indicated that rearing the house cricket Acheta domesticus on byproduct is possible. However, it is important to fulfill the crickets need of nutrients to increase the growth and survival rate of the house cricket. Homo-geneity and uniformity of feed is important to increase acceptability. Beyond the feed, farming temperature and relative humidity needs to be optimised, to increase the production of the house crickets.